2017
DOI: 10.14366/usg.16048
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic imaging of papillary thyroid carcinoma variants

Abstract: Ultrasonography (US) is routinely used to evaluate thyroid nodules. The US features of papillary thyroid carcinoma (PTC), the most common thyroid malignancy, include hypoechogenicity, spiculated/microlobulated margins, microcalcifications, and a nonparallel orientation. However, many PTC variants have been identified, some of which differ from the classic type of PTC in terms of biological behavior and clinical outcomes. This review describes the US features and clinical implications of the variants of PTC. Wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
58
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(66 citation statements)
references
References 47 publications
5
58
0
3
Order By: Relevance
“…Papillary thyroid carcinoma (PTC) is the most common type of thyroid malignancy, with an indolent clinical course and a favorable prognosis ( 1 , 2 ). Several PTC subtypes exhibiting a combination of specific growth patterns, cell types, stromal changes, and nuclear features have been documented ( 3 ). In the revised American Thyroid Association guidelines ( 4 ), PTC is classified into three major subtypes according to the biological behavior: subtypes associated with aggressive outcomes, including the tall cell, columnar cell, and hobnail variants; subtype associated with less favorable outcomes, including the solid and diffuse sclerosing variants; and subtype associated with favorable outcomes, including the follicular, cribriform–morular, and Warthin-like variants.…”
Section: Introductionmentioning
confidence: 99%
“…Papillary thyroid carcinoma (PTC) is the most common type of thyroid malignancy, with an indolent clinical course and a favorable prognosis ( 1 , 2 ). Several PTC subtypes exhibiting a combination of specific growth patterns, cell types, stromal changes, and nuclear features have been documented ( 3 ). In the revised American Thyroid Association guidelines ( 4 ), PTC is classified into three major subtypes according to the biological behavior: subtypes associated with aggressive outcomes, including the tall cell, columnar cell, and hobnail variants; subtype associated with less favorable outcomes, including the solid and diffuse sclerosing variants; and subtype associated with favorable outcomes, including the follicular, cribriform–morular, and Warthin-like variants.…”
Section: Introductionmentioning
confidence: 99%
“…Our study demonstrates that the use of TI-RADS reduces the number of unnecessary biopsies and has the benefit of minimizing the burden on patients. The use of a relatively large cutoff size for biopsy of low-suspicion or mildly suspicious nodules is justified because the incidence of aggressive thyroid cancers as well as the malignancy risk is relatively low in these nodules (1,2).…”
mentioning
confidence: 99%
“…Several studies reported that, prognosis of patients with PTCs may be associated with both clinical features and pathological variants [13][14][15]. However, US characters of various PTC subgroups are still insufficient [15,16], even though the method was widely used as the primary method in evaluating thyroid lesions.…”
Section: Discussionmentioning
confidence: 99%